Advanced information systems engineering : 30th International Conference, CAiSE 2018, Tallinn, Estonia, June 11-15, 2018, Proceedings /: 30th International Conference, CAiSE 2018, Tallinn, Estonia, June 11-15, 2018, Proceedings. (2018) - Unknown
No abstract available